2017
DOI: 10.1186/s13027-017-0140-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with sexually transmitted infections (STIs) among women of reproductive age in Swaziland

Abstract: BackgroundSexually transmitted infections (STIs) remain an important public health problem with approximately half a billion new cases annually among persons aged 15–49 years. Epidemiological data on STIs among women of reproductive age in Swaziland are limited. The availability of epidemiological data on STIs and associated risk factors in this population is essential for the development of successful prevention, diagnosis and management strategies in the country. The study aimed to determine the prevalence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 50 publications
(59 reference statements)
15
45
1
Order By: Relevance
“…The proportion of cases that used sexual enhancers compared with cases who did not was 40.3% to 19.7%. This fi ndings corresponds with studies carried out by Ginindza, et al, [6], Men´endez et al, [10], Hughes, et al, [11], where risk factors for STI which were signifi cant were alcohol consumption and having more than one sexual partner, having the partner living in another area, number of sexual partners and ever injected drugs respectively. In addition, studies by Saroj, Murthy, Kumar, & Kumar [9], which stated that a signifi cantly higher proportion of cases liked to take alcohol/illicit drugs while having sex (46/106, 43.4% cases vs. 6/45, 13.3% controls, P<0.001) with an Odds ratio of 17.538 for those who had a history of alcohol intake supported this study fi ndings.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The proportion of cases that used sexual enhancers compared with cases who did not was 40.3% to 19.7%. This fi ndings corresponds with studies carried out by Ginindza, et al, [6], Men´endez et al, [10], Hughes, et al, [11], where risk factors for STI which were signifi cant were alcohol consumption and having more than one sexual partner, having the partner living in another area, number of sexual partners and ever injected drugs respectively. In addition, studies by Saroj, Murthy, Kumar, & Kumar [9], which stated that a signifi cantly higher proportion of cases liked to take alcohol/illicit drugs while having sex (46/106, 43.4% cases vs. 6/45, 13.3% controls, P<0.001) with an Odds ratio of 17.538 for those who had a history of alcohol intake supported this study fi ndings.…”
Section: Discussionsupporting
confidence: 90%
“…When socio-demographic characteristics were considered in this study, result showed being single as a risk factor for STIs was signifi cantly associated with STI morbidity. Previous studies by [6], which stated that being married (OR=0.4, 95% CI: 0.3-0.7) is inversely associated with STIs and [7], which stated that being single is directly associated with STIs [Odds Ratio (OR) 1.82, (95% CI 1.08, 3.05)] supported this fi nding. The reason for this may be because single persons are more likely to have multiple sexual relationships than married persons.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…All aPRs and 95% CIs were adjusted for age, marital status, education, history of known syphilis infection, and previous pregnancy. These variables were selected a priori based on the existing literature [13,26,27]. All statistical analyses were conducted using SAS 9.4 (SAS Institute Inc., Cary, NC).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…It is the most common, non-viral, sexually transmitted agent worldwide, responsible for 143 million cases in 2012 and 110.4 million in 2018 [2]. Epidemiological studies have shown that TV infection can lead to an increased risk of cervical cancer [13][14][15][16]. The interaction between cervical cancer and TV is not yet fully elucidated, but it is believed that the in ammatory process caused by this protozoan predisposes the epithelium to carcinogenesis [12,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%